Synthesis, characterization and biological studies of dithiocarbamate derivatives and their metal complexes - Rahima (Kulliyyah of Science, International Islamic University Malaysia, 2015)
Three N–monosubstituted dithiocarbamates [potassium phenylethyl dithiocarbamate (PEDTC), 2–phenylethanaminium phenylethyl dithiocarbamates (APEDTC), and 3–phenylpropyl dithiocarbamate (PPDTC)] and three N–disubstituted dithiocarbamates [potassium bis(2–hydroxyethyl) dithiocarbamte (HEDTC), sodium piperidine dithiocarbamate (PDTC) and sodium morpholine dithiocarbamate (MDTC)], four series of S–substituted dithiocarbamate derivatives from PEDTC, PPDTC, PDTC, and MDTC, and metal complexes of HEDTC and PEDTC were successfully synthesized and characterized. Nickel complexes derived from S2MPEDT and SNMPEDT were found to be disulfane ligands [1,2–bis(2–methylbenzyl)disulfane (B2MSS) and 1,2–bis(naphthalen–2–ylmethyl)disulfane (BNMSS)]. Imidazolidine–2–thione (NAPH2T) was obtained unexpectedly from the attempt to synthesize N–monosubstituted dithiocarbamate. All compounds possessed yields ranging from low to good. Nineteen structures were elucidated using single crystal X–ray diffraction analysis. S–substituted derivatives were synthesized from nucleophilic substitution of sodium or potassium dithiocarbamates with a variety of alkyl halides (benzyl chloride, 2–methylbenzyl chloride, 3–methylbenzyl chloride, 4–methylbenzyl chloride, and 1–chloromethylnaphtalene). The antimicrobial activities of all the N–, S–substituted dithiocarbamates and their complexes were investigated against four gram–positive bacteria (B. cereus, S. aureus, S. epidermidis, and S. pyogenes), four gram–negative bacteria (E. coli, K. pneumonia, P. aeruginosa, and S. typhimurium), and fungi (C. albicans). It was found that the S–substituted derivatives were active selectively against S. epidermidis and S. pyogenes. For S. epidermidis, the inhibition zones (mm) were 7 ± 0 (S2MPEDT), 9 ± 0 (S3MPEDT), 8 ± 0.6 (SNMPEDT), (9 ± 0) SBPPDT, (9 ± 0) S3MPPDT, (8 ± 0) S4MPPDT, and (11 ± 0) S3MPDT. The inhibition zones (mm) of 7 ± 0.6 (SBPEDT), 8 ± 0.6 (S2MPEDT), 10 ± 1.1 (S3MPEDT), 8 ± 0.6 (S4MPEDT), 8 ± 0 (SNMPEDT), and 11 ± 1.4 (SBPPDT) were recorded against S. pyogenes. The N–substituted dithiocarbamates showed activity against C. albicans with inhibition zone (mm) of 13 ± 0.57 (HEDTC), 15 ± 0 (PEDTC), 14 ± 0 (APEDTC), 16 ± 0 (PDTC), and 15 ± 0 (MDTC). Cytotoxic activity was assayed against p53–positive and negative non–small human lung cancer cell line (A549 and H1299), and breast cancer oestrogen receptor positive cell line (MCF–7). The S–substituted derivatives were selectively cytotoxic, while the complexes were more cytotoxic compared to their parent ligands, specifically for Cu(HEDTC)2, Pb(HEDTC)2, Ni(PEDTC)2, Ni(B2MSS), and Ni(BNMSS) complexes toward H1299, with IC50 of 25 μM, 90 μM, 4.5 μM, 41 μg/ml, and 32.5 μg/ml, respectively.